EVA hot melt adhesive for wooden board surface veneer and preparation process thereof

By reasonably preparing EVA hot melt adhesive, the shortcomings of existing wooden board surface veneer adhesives in terms of drying speed and bonding strength are solved, and the effects of rapid drying, high bonding strength and good stability are achieved. They are suitable for the surface veneer of wooden boards.

CN115895507BActive Publication Date: 2025-04-11SHANGHAI ROCKY ADHESIVES CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211383739.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-07
Publication Date
2025-04-11
Estimated Expiration
2042-11-07

AI Technical Summary

Technical Problem

The existing wooden board surface veneer adhesives have shortcomings in terms of drying speed and bonding strength, and the production process is complicated, making it difficult to adapt to large-scale processing.

Method used

Using EVA hot melt adhesive as the main raw material, by reasonably preparing EVA resin, polyolefin, tackifier, wax and antioxidant, hot melt adhesive with short opening time, fast drying, high bonding strength and good stability were prepared.

Benefits of technology

It realizes rapid drying and high bonding strength of hot melt adhesive, is suitable for continuous production, does not contain formaldehyde, has low VOC content, is stable at high and low temperatures, and is suitable for the surface veneer of wooden boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003928946670000111
    Figure BDA0003928946670000111
Patent Text Reader

Abstract

The present invention relates to the field of hot melt adhesive technology, in particular to the field of IPC C 09J7, and more specifically to an EVA hot melt adhesive for surface veneer of a wooden board and a preparation process thereof. The EVA hot melt adhesive for surface veneer of a wooden board comprises, by weight, 30-60 parts of EVA resin, 10-30 parts of polyolefin, 30-45 parts of tackifier, 5-20 parts of wax, and 0.05-0.5 parts of antioxidant. The prepared hot melt adhesive has a short open time, fast drying, high production efficiency, is suitable for continuous production, does not contain formaldehyde, has an extremely low VOC content, has good stability at high and low temperatures, and is particularly suitable for surface veneer of wooden boards such as medium density boards, particle boards, and plywood.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hot melt adhesives, in particular to the field of IPC C 09J7, and more specifically to an EVA hot melt adhesive for surface veneer of a wooden board and a preparation process thereof. Background Art

[0002] Furniture production, especially custom furniture production, often uses medium density fiberboard, particleboard, plywood and other boards for processing and production. Most of the board surfaces need to be finished, that is, paper, veneer, PVC film and other materials are attached to the board surface to achieve a beautiful effect. The traditional method of attaching paper, veneer, PVC film and other materials on the board surface generally uses urea-formaldehyde resin glue, white latex, wood glue powder and other glues. These glues dry slowly, resulting in low efficiency, poor bonding strength, and are not environmentally friendly, affecting people's life experience.

[0003] In the prior art, a patent application document with application publication number CN 104140773 A discloses a repairable veneer adhesive and a synthesis method thereof. By adding raw materials such as bis(N-ethyleneureaethyl)maleate, industrial gelatin, methacrylic acid, and N-hydroxyethylacrylamide, the bonding strength is increased, so that the adhesive has a certain repair function. However, the adhesive has a large number of raw materials, complicated steps, and is not easy to process on a large scale.

[0004] The patent application document with application publication number CN 101343521A discloses a method for preparing a functional veneer veneer adhesive. By selecting phenolic resin, polyester resin and nano-titanium dioxide, an adhesive with high strength and good water resistance is obtained, but its open time is long.

[0005] To solve the above problems, this patent proposes an EVA hot melt adhesive for wooden board surface veneer and its preparation process. The prepared hot melt adhesive has a short open time, fast drying, high production efficiency, is suitable for continuous production, does not contain formaldehyde, has an extremely low VOC content, and has good stability at both high and low temperatures. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present invention provides an EVA hot melt adhesive for surface veneer of wooden boards. The raw materials for preparation include, by weight: 30-60 parts of EVA resin, 10-30 parts of polyolefin, 30-45 parts of tackifier, 5-20 parts of wax, and 0.05-0.5 parts of antioxidant.

[0007] Preferably, the content of vinyl acetate in the EVA resin is 20-40wt%, and the melt index is 10-50g / 10min; further preferably, the content of vinyl acetate in the EVA resin is 28wt%, and the melt index is 43g / 10min.

[0008] In some preferred embodiments, the EVA resin may be commercially available, such as Elvax Eva-240W produced by DuPont Company of the United States.

[0009] In some preferred schemes, the use of specific EVA resins can improve the flexibility and bonding properties of hot melt adhesives, and is suitable for application in wooden board surface veneer. This is because the introduction of ethylene will increase the distance between carboxyl groups in the polymer chain and lengthen the side chains, thereby reducing steric hindrance and improving the softness of the polymer chain, so that the prepared hot melt adhesive has a certain flexibility. At the same time, ethylene and vinyl acetate work synergistically to improve the polarity of the hot melt adhesive, thereby improving the bonding properties of the hot melt adhesive. However, too high ethylene content will reduce the hardness and water resistance of the hot melt adhesive. In order to ensure that the EVA resin can meet the viscosity and flexibility of the EVA hot melt adhesive for wooden board surface veneer, the content of vinyl acetate in the EVA resin is 20-40wt%, and the melt index is 10-50g / 10min. However, with only EVA resin as the raw material, the bonding strength of the hot melt adhesive is still not high.

[0010] Preferably, the polyolefin is one or more of ethylene-octene copolymer, polypropylene, polyethylene; more preferably, it is ethylene-octene copolymer.

[0011] The melt index of the ethylene-octene copolymer at 190°C is 0.2-5.0 g / 10 min, and the Mooney viscosity at 121°C is 15-30 MU; more preferably, the melt index of the ethylene-octene copolymer at 190°C is 1.0 g / 10 min, and the Mooney viscosity at 121°C is 22 MU.

[0012] In some preferred embodiments, the ethylene-octene copolymer may be commercially available, such as POE 8003 produced by Dow Chemical of the United States.

[0013] The applicant unexpectedly discovered that the addition of specific polyolefins can work synergistically with other raw materials in the system, not only improving the high and low temperature resistance of the EVA hot melt adhesive, but also preventing carbonization at high temperatures and maintaining stable performance.

[0014] Preferably, the tackifier is one or more of aliphatic petroleum resin, alicyclic petroleum resin, rosin resin, aromatic petroleum resin, hydrogenated rosin resin, and terpene resin; more preferably, it is aliphatic petroleum resin.

[0015] Preferably, the aliphatic petroleum resin is aliphatic hydrogenated petroleum resin.

[0016] Preferably, the softening point of the tackifier is 90-110° C., and the melt viscosity is 100-150 cps; further preferably, the softening point of the tackifier is 100° C., and the melt viscosity is 133 cps.

[0017] In some preferred embodiments, the tackifier may be commercially available, such as LH100-1Y produced by Shandong Luhua Energy Group Co., Ltd.

[0018] The applicant found that the use of aliphatic petroleum resin as a tackifier can not only make the hot melt adhesive have good flexibility, but also improve the bonding strength of the hot melt adhesive, and the VOC content is low. This is because aliphatic petroleum resin has high thermal stability and tackifying properties, has high compatibility with ethylene-vinyl acetate copolymer emulsion, can improve the wettability of hot melt adhesive to the adherend, thereby improving the bonding strength of hot melt adhesive, and its odor is small, making the VOC content in the hot melt adhesive extremely low, which is very suitable for application on the surface veneer of wooden boards on furniture. It also does not contain formaldehyde and is not harmful to the human body, but its stability is poor. The applicant unexpectedly found that hydrogenating aliphatic petroleum resin can improve the stability of hot melt adhesive. This may be because the hydrogenation reaction converts unsaturated hydrocarbons in aliphatic petroleum resin into saturated hydrocarbons, thereby improving the stability of hot melt adhesive. In order to ensure that aliphatic petroleum resin can meet the viscosity and stability of EVA hot melt adhesive for wooden board surface veneer, the softening point of the tackifier is 90-110°C and the melt viscosity is 100-150cps.

[0019] Preferably, the weight ratio of the EVA resin to the tackifier is 1:(0.5-1); further preferably, it is 5:4.

[0020] Preferably, the wax is one or more of paraffin wax, microcrystalline wax, polypropylene wax, polyethylene wax, EVA synthetic wax, and Fischer-Tropsch wax; further preferably, it is Fischer-Tropsch wax and microcrystalline wax.

[0021] Preferably, the mass ratio of the Fischer-Tropsch wax to the microcrystalline wax is 1:(0.5-3); further preferably, it is 1:1.

[0022] Preferably, the softening point of the Fischer-Tropsch wax is 90-110°C, and the viscosity at 140°C is 5-10cps; further preferably, the softening point of the Fischer-Tropsch wax is 100-105°C, and the viscosity at 140°C is 5-10cps.

[0023] In some preferred embodiments, the Fischer-Tropsch wax may be commercially available, such as SN9118 produced by Qingdao Sino New Materials Co., Ltd.

[0024] Preferably, the melting point of the microcrystalline wax is 60-100°C, and the kinematic viscosity at 100°C is 10-20 mm 2 / s; Further preferably, the melting point of the microcrystalline wax is 69-90°C, and the kinematic viscosity at 100°C is 13-18mm 2 / s.

[0025] In some preferred embodiments, the microcrystalline wax may be commercially available, such as microcrystalline wax produced by Henan Yuyang Wax Co., Ltd.

[0026] Preferably, the weight ratio of the wax to the EVA resin is 1:(2-10); further preferably, it is 1:5.

[0027] Usually paraffin is used as wax in hot melt adhesives to act as a regulator, but paraffin has a low softening point and poor dispersibility. When the temperature is too high, the paraffin will liquefy and agglomerate, affecting its use. The applicant has found that the use of Fischer-Tropsch wax as wax can improve the high-temperature stability of hot melt adhesives. This may be because Fischer-Tropsch wax has a high degree of crystallinity and contains a large number of n-alkane structures, so that the prepared hot melt adhesive is not only resistant to high temperatures, but also can shorten the curing time of the hot melt adhesive, but its low-temperature resistance is poor. The applicant unexpectedly found that when a certain amount of microcrystalline wax is added and the mass ratio of Fischer-Tropsch wax to microcrystalline wax is 1: (0.5-3), the obtained hot melt adhesive not only has high-temperature stability, but also has low-temperature stability, and can save production costs, with high economic benefits. This is because the microcrystalline wax molecules have branched and ring structures, a wide distribution of carbon atoms, low molecular crystallinity and the presence of amorphous regions. They can work synergistically with Fischer-Tropsch wax to improve the high and low temperature stability of the hot melt adhesive while reducing the open time. They are pollution-free, have low viscosity at high temperatures, and can also improve the fluidity of the hot melt adhesive and enhance the wettability of the bonding surface, thereby further improving the bonding strength of the hot melt adhesive.

[0028] Preferably, the antioxidant is selected from one or more of hindered phenol antioxidants, thioether antioxidants, hydroxylamine antioxidants, and phosphite antioxidants; further preferably, hindered phenol antioxidants and phosphite antioxidants.

[0029] Preferably, the weight ratio of the hindered phenol antioxidant to the phosphite antioxidant is (1-5):1; more preferably, it is 3:1.

[0030] Preferably, the main component of the hindered phenol antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl, 2,4,6,-tris(3,5,-di-tert-butyl, 4-hydroxybenzyl)benzene, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid; further preferably, it is tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester.

[0031] In some preferred embodiments, the hindered phenol antioxidant may be commercially available, such as Irganox 1010 produced by BASF Corporation of the United States.

[0032] Preferably, the main component of the phosphite antioxidant is one or more of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, and 2,2'-methylenebis(4,6-di-tert-butylphenyl)isooctyloxyphosphite; further preferably, it is tris(2,4-di-tert-butylphenyl)phosphite.

[0033] In some preferred embodiments, the phosphite antioxidant may be commercially available, such as Irganox 168 produced by BASF Corporation of the United States.

[0034] Hot melt adhesives will age due to environmental factors such as oxygen, light, and heat, especially when hot melt adhesives are prepared at high temperatures, the aging phenomenon is more serious. Therefore, antioxidants need to be added to the raw materials of hot melt adhesives to prevent aging. Currently, most of them use hindered phenol antioxidants, but their antioxidant effect is single, and in the process of inhibiting oxidative degradation, hydroperoxides will be produced. Hydroperoxides are unstable, and they cannot decompose hydroperoxides by themselves, so there is still an aging risk when used alone. The applicant unexpectedly discovered that the use of hindered phenol antioxidants and phosphite antioxidants in a weight ratio of (1-5): 1 as antioxidants can greatly improve the anti-aging ability of hot melt adhesives. This may be because the addition of a certain amount of phosphite antioxidants can work synergistically with hindered phenol antioxidants, not only decomposing free radicals to inhibit oxidative degradation, but also decomposing unstable products of oxidative degradation, thereby improving the antioxidant properties of the hot melt adhesive. Both antioxidants are compatible with ethylene-vinyl acetate copolymer emulsions, and have good functions of inhibiting and delaying oxidation without affecting the bonding strength of the hot melt adhesive, and will not cause discoloration or stratification of the hot melt adhesive.

[0035] The second aspect of the present invention provides a process for preparing the EVA hot melt adhesive for surface veneer of a wooden board as described above, comprising the following steps:

[0036] Mix the tackifier and antioxidant and heat to 80-100°C, stir until the solution is homogeneous and transparent, add wax, and after the sample is completely melted, increase the temperature to 130-160°C, add EVA resin and polyolefin, continue stirring for 2-3 hours, and cool to 20-30°C to obtain the product.

[0037] Beneficial effects:

[0038] 1. By selecting EVA resin with a vinyl acetate content of 20-40wt% and a melt index of 10-50g / 10min as the EVA resin, the flexibility and bonding performance of the hot melt adhesive can be improved, and it is suitable for application in surface veneer of wooden boards.

[0039] 2. By selecting hydrogenated aliphatic petroleum resin with a softening point of 90-110°C and a melt viscosity of 100-150cps as a tackifier, not only can the hot melt adhesive have good flexibility, but also the bonding strength and stability of the hot melt adhesive can be improved, and the VOC content is low.

[0040] 3. By selecting Fischer-Tropsch wax and microcrystalline wax in a mass ratio of 1: (0.5-3) as wax, the high and low temperature stability of the hot melt adhesive is improved while reducing the open time, and it is pollution-free, has low viscosity at high temperatures, and can also improve the fluidity of the hot melt adhesive and enhance the wettability of the bonding surface, thereby further improving the bonding strength of the hot melt adhesive.

[0041] 4. By selecting a hindered phenol antioxidant and a phosphite antioxidant in a weight ratio of (1-5):1 as antioxidants, while not affecting the bonding strength of the hot melt adhesive, they have good functions of inhibiting and delaying oxidation and will not cause discoloration, stratification, etc. of the hot melt adhesive.

[0042] 5. The EVA hot melt adhesive for surface veneering of wooden boards prepared by the present invention is not only suitable for furniture boards, such as medium-density fiberboard, particleboard, plywood, etc., but also suitable for paper product processing, cigarette glue, flexible packaging, textiles, envelopes, box sealing, non-woven fabrics and other fields. DETAILED DESCRIPTION

[0043] Example

[0044] Example 1

[0045] Example 1 provides an EVA hot melt adhesive for surface veneer of wooden board. The raw materials for its preparation include, by weight: 50 parts of EVA resin, 20 parts of polyolefin, 40 parts of tackifier, 10 parts of wax, and 0.4 parts of antioxidant.

[0046] The EVA resin is EVA resin.

[0047] The content of vinyl acetate in the EVA resin is 28 wt % and the melt index is 43 g / 10 min.

[0048] The EVA resin was purchased from Elvax Eva-240W produced by DuPont Company, USA.

[0049] The polyolefin is an ethylene-octene copolymer.

[0050] The ethylene-octene copolymer has a melt index of 1.0 g / 10 min at 190° C. and a Mooney viscosity of 22 MU at 121° C.

[0051] The ethylene-octene copolymer was purchased from a supplier, POE 8003 produced by Dow Chemical, USA.

[0052] The tackifier is aliphatic petroleum resin.

[0053] The aliphatic petroleum resin is an aliphatic hydrogenated petroleum resin.

[0054] The tackifier has a softening point of 100° C. and a melt viscosity of 133 cps.

[0055] The tackifier was purchased from a supplier, Shandong Luhua Energy Group Co., Ltd., and was produced by LH100-1Y.

[0056] The waxes are Fischer-Tropsch wax and microcrystalline wax.

[0057] The mass ratio of the Fischer-Tropsch wax to the microcrystalline wax is 1:1.

[0058] The softening point of the Fischer-Tropsch wax is 100-105° C., and the viscosity at 140° C. is 5-10 cps.

[0059] The Fischer-Tropsch wax was purchased from supplier Qingdao Sino New Materials Co., Ltd., which produces SN9118.

[0060] The melting point of the microcrystalline wax is 69-90°C, and the kinematic viscosity at 100°C is 13-18 mm 2 / s.

[0061] The microcrystalline wax was purchased from the microcrystalline wax produced by Henan Yuyang Wax Co., Ltd., a supplier.

[0062] The antioxidants are hindered phenol antioxidants and phosphite antioxidants.

[0063] The weight ratio of the hindered phenol antioxidant to the phosphite antioxidant is 3:1.

[0064] The main component of the hindered phenol antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0065] The hindered phenol antioxidant was purchased from a supplier, Irganox 1010 produced by BASF Corporation of the United States.

[0066] The main component of the phosphite antioxidant is tris(2,4-di-tert-butylphenyl) phosphite.

[0067] The phosphite antioxidant was purchased from a supplier, Irganox 168 produced by BASF Corporation of the United States.

[0068] A second aspect of the present invention provides a method for preparing the EVA hot melt adhesive for veneer on the surface of a wooden board as described above, comprising the following steps:

[0069] Mix the tackifier and antioxidant and heat to 100°C, stir until the solution is homogeneous and transparent, then add wax. After the sample is completely melted, raise the temperature to 150°C, add EVA resin and polyolefin, continue stirring for 2.5 hours, and then cool to 25°C to obtain the product.

[0070] Example 2

[0071] Example 2 provides an EVA hot melt adhesive for surface veneer of wooden boards. The specific implementation method is the same as that of Example 1, except that: 30 parts of EVA resin, 10 parts of polyolefin, 30 parts of tackifier, 5 parts of wax, and 0.05 parts of antioxidant.

[0072] The mass ratio of the Fischer-Tropsch wax to the microcrystalline wax is 2:1.

[0073] The weight ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:1.

[0074] Example 3

[0075] Example 3 provides an EVA hot melt adhesive for surface veneer of wooden boards. The specific implementation method is the same as that of Example 1, except that: 60 parts of EVA resin, 30 parts of polyolefin, 45 parts of tackifier, 20 parts of wax, and 0.5 parts of antioxidant.

[0076] The mass ratio of the Fischer-Tropsch wax to the microcrystalline wax is 1:3.

[0077] The weight ratio of the hindered phenol antioxidant to the phosphite antioxidant is 5:1.

[0078] Example 4

[0079] Example 4 provides an EVA hot melt adhesive for surface veneer of wooden board. The specific implementation method is the same as that of Example 1, except that the tackifier is an aromatic petroleum resin.

[0080] The tackifier was purchased from a supplier, pht-T1080 produced by Puyang Hengtai Petrochemical Co., Ltd.

[0081] Example 5

[0082] Example 5 provides an EVA hot melt adhesive for surface veneer of wooden board. The specific implementation method is the same as that of Example 1, except that the antioxidant is a hindered phenol antioxidant.

[0083] Performance Testing Methods

[0084] 1. Shear strength

[0085] The surface veneer of the wooden board prepared in Examples 1-5 was veneered with EVA hot melt adhesive. After heating to 140°C, it was bonded to two 100mm×75mm×75mm plywood test blocks, where the area of ​​the bonding surface was 75mm×75mm, and the amount of glue applied was 2g of mixed glue. After standing for 24 hours, the shear strength was measured using the national standard GB / T 17657-2013, and the results are recorded in Table 1.

[0086] 2. Immersion peeling test

[0087] The surface veneer of the wooden board prepared in Examples 1-5 was veneered with EVA hot melt adhesive, heated to 140°C, and then bonded to two 100mm×75mm×75mm plywood test blocks, where the bonding surface area was 75mm×75mm, and the amount of glue applied was 2g of mixed glue. After standing for 24 hours, the immersion peeling strength was measured using the national standard GB / T 17657-2013, and the peeling and delamination of the glue layer were observed. The peeling rate of the wooden board was less than 10% and the glue line debonding rate was less than one-third, which was qualified. The number of samples in Examples 1-5 was 10, a total of 50 samples, and 200 glue lines. The peeling of the wooden board was the separation between the two wooden boards, and the glue line debonding rate of the board was the number of samples separated / 50*100%; the cumulative length of the peeled part of each edge of each glue layer was greater than 0.3mm, which was the glue line debonding, and the glue line debonding rate was the number of glue layers with glue line debonding / 200*100%. The results of Examples 1-5 are recorded in Table 1.

[0088] 3. High and low temperature stability

[0089] High temperature stability:

[0090] The surface veneer of the wooden board prepared in Examples 1-5 was veneered with EVA hot melt adhesive. After the temperature was raised to 140°C, it was bonded to two 100mm×30mm×20mm plywood test blocks, where the area of ​​the bonding surface was 30mm×20mm, and the amount of glue applied was 1g of mixed glue. After standing for 24 hours, the high temperature stability was determined using the national standard GB / T 17657-2013. The specimen was placed in a 120°C forced air drying oven and dried for 2 hours, then taken out and the surface condition of the specimen was observed.

[0091] Low temperature stability:

[0092] The surface veneer of the wooden board prepared in Examples 1-5 was veneered with EVA hot melt adhesive. After heating to 140°C, it was bonded to two 100mm×30mm×20mm plywood test blocks, where the area of ​​the bonding surface was 30mm×20mm, and the amount of glue applied was 1g of mixed glue. After standing for 24 hours, the high temperature stability was determined using the national standard GB / T 17657-2013. The specimen was placed in a -20°C forced air drying oven and dried for 2 hours, then taken out and the surface condition of the specimen was observed.

[0093] 4. VOC content test

[0094] The VOC content of the EVA hot melt adhesive for surface veneer of the wooden board prepared in Examples 1-5 was measured using GB 33372-2020, and the results are recorded in Table 1.

[0095] Table 1

[0096]

Claims

1. An EVA hot melt adhesive for veneer on wooden board surface, characterized in that: The raw materials for its preparation include, by weight: 30-60 parts of EVA resin, 10-30 parts of polyolefin, 30-45 parts of tackifier, 5-20 parts of wax, and 0.05-0.5 parts of antioxidant; the content of vinyl acetate in the EVA resin is 28wt%, and the melt index is 43g / 10min; the polyolefin is ethylene-octene copolymer, the melt index of the ethylene-octene copolymer at 190°C is 0.2-5.0g / 10min, and the Mooney viscosity at 121°C is 15-30MU; the tackifier is an aliphatic petroleum resin, and the aliphatic petroleum resin is an aliphatic hydrogenated petroleum resin; the softening point of the tackifier is 90-110°C, and the melt viscosity is 100-150cps; the wax is Fischer-Tropsch wax and microcrystalline wax, and the mass ratio of the Fischer-Tropsch wax to the microcrystalline wax is 1:(0.5-3); the antioxidant is a hindered phenol antioxidant and a phosphite antioxidant, and the weight ratio of the hindered phenol antioxidant to the phosphite antioxidant is (1-5):

1.

2. The EVA hot melt adhesive for surface veneer of a wooden board according to claim 1, characterized in that: The weight ratio of the EVA resin to the tackifier is 1:(0.5-1).

3. The EVA hot melt adhesive for surface veneer of a wooden board according to claim 2, characterized in that: The weight ratio of the wax to the EVA resin is 1:(2-10).

4. A process for preparing an EVA hot melt adhesive for surface veneer of a wooden board according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mix the tackifier and antioxidant and heat to 100-150°C, stir until the solution is homogeneous and transparent, add wax, and after the sample is completely melted, increase the temperature to 130-160°C, add EVA resin and polyolefin, continue stirring for 2-3 hours, and cool to 20-30°C to obtain the product.

Citation Information

Patent Citations

  • Preparation method for functional single-sided laminated sheet glue

    CN101343521A

  • Repairable veneer adhesive and synthesizing method thereof

    CN104140773A

  • Furniture edge sealing glue and preparation method thereof

    CN109096951A

  • Preparation method of high-temperature-resistant thermoplastic hot melt adhesive for furniture edge sealing

    CN110343490A

  • Hot melt adhesive for decorative wood veneer coated wood sectional bar and production process of the hot melt adhesive

    CN111073552A